The Effect Of Explicit Instruction On Formulaic Sequences And Working Memory On Intermediate Malaysian Esl Learners᾽ Oral Fluency - Orang, Maryam (2019)
Most Malaysian university graduates still experience difficulties in their work place because of their poor English language, mainly in speaking skill. Many researchers have claimed that the use of formulaic sequences facilitates the students̕ oral production and increases their L2 oral fluency, especially the low proficient L2 learners when they are not able to create new sentences or retrieve the appropriate vocabularies. In this study, efforts were made to investigate the effect of the explicit instruction of formulaic sequences on Malaysian L2 learners᾽oral fluency while considering the role of their working memory capacity, as one of the important effective factors in learning language, on their use of formulaic sequences and their L2 oral fluency. Therefore, a sample of 54 students in their second semester of academic session 2015-2016, enrolled in a preparatory English language course, were selected through purposive sampling. They were assigned to two groups including the treatment group (28 participants) and the non-treated group (26 participants). Both samples were pre-tested for the homogeneity in their performance on the temporal variables of L2 oral fluency and their use of formulaic sequences through a spontaneous narrative monologue test which was followed by a specific treatment incorporated in the normal contents of the preparatory English language course for the treatment group and lasted for fifteen three-hour sessions. However, the control group received only the normal contents of the preparatory English language course.